MENINGKATKAN HASIL BELAJAR AL-QUR’AN HADIST MELALUI PENERAPAN METODE CARD SORT PADA POKOK BAHASAN SURAT AT-TIN BAGI SISWA-SISWI KELAS III MI MA’ARIF PANJENG JENANGAN PONOROGO SEMESTER GENAP TAHUN PELAJARAN 2016-2017 - Mujiono Mujiono; Rido Kurnianto; Wahyudi Setiawan (Universitas Muhammadiyah Ponorogo, 2017)
Starting from the condition of learning al-Qur'an Hadist class III MI Ma'arif Panjeng shows teachers still use conventional methods such as lecture methods and occasional interrupted question and answer. Teachers dominate more in the learning activities, while students just sit and pay attention to the teacher's explanation of the subject matter presented by the teacher does not use learning methods that appeal to students to be active in learning activities. This causes the students' interest and motivation to be low so that it impacts on the learning outcomes of the low Hadith Qur'an. These conditions need to be improved by appropriate learning methods in order to improve the learning outcomes of al-Qur'an Hadist one of them with Card Sort method.In describing the application of the method of